The Additional Diagnostic Value of the Three-dimensional 3D ultrasound and Doppler angiography imaging in the prenatal diagnosis of left isomerism - Wael, El Guindi; Michel, Dreyfus; Gabriel, Carle; Nidal, Alassas (Journal of Clinical Case Reports and Images, 2020)
Objective To highlight the value of 3D ultrasound and Doppler angiography imagingin the prenatal assessment of left fetal isomerism. Methods A retrospective offline analysis of volume datasets of 3 fetuses with left atrial isomerism by 3D ultrasound was conducted. Conclusion We believe that parasagittal view demonstrating the heart and the abdominal vessels is easy to obtain and interpret, offer a realistic anatomic image, needs no mental reconstruction of spatial relationships and is very beneficial mainly in detecting the situs. We propose to use 3D ultrasound systematically in suspected cases of atrial isomerism, and better understand and interpret fetal anatomy.
Keywords: Heterotaxy; Isomerism; Polysplenia; Asplenia; Situs ambigus; Situs inversus; Situs solitus; Cardiovascular malformations; Power Doppler imaging; 3D ultrasound. Left atrial isomerism. Malrotation.